Trade, Technologies and the Talent Organization - Jan Schymik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper introduces the theory of firm organization under moral hazard into an equilibrium model of international trade with heterogeneous talents and technologies. The model is able to explain how the allocation of power and the provision of financial incentives inside firms varies within and across industries. Variation in the value of outside options triggers owners to choose different levels of firm organization and financial incentives. While incentive compensation and centralized decision-making are substitutes for human capital scarce firms, human capital intensive firms use incentive compensation and the delegation of power as complements to keep their managers participating. Trade liberalizations and skill-biased technological changes affect the distribution of outside options and thus let firms reorganize and provide different financial incentives. Trade integrations may lead firms to endogenously choose organizations with powerful managers and consequently managerial entrenchment arises in the most productive firms.
Keywords: F12; L22; D23; 330